Rear or east-facing elevation of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is the rear or east-facing elevation of the Mahanaleshwar Temple, reflecting the bhumija temple shikhara (superstructure). All four sides of the shikhara have cardinal bands, called lata, at the centre. The four quadrants which are formed in between these are filled with rows of miniature shikharas or bhumis. These have motifs of the details of the main shikhara. The base of the lata has an ornamental window, and a chaitya dormer with a miniature motif of a kutastambha in it.